Gut-Brain-Microbiota Axis and Hypertension: A Literature Review - Kwon, Young N.; Kim, Yong-Jae (Current Pharmaceutical Design, 2021)
The gut and brain are linked via various bidirectional pathways, and they communicate withand affect each other. The interaction between the gut-brain axis and the gut microbiota has attracted much attention in the development of hypertension. In this review, we have discussed the gut-brain-microbiota axis and its association with gut dysbiosis in terms of regulation of blood pressure using the autonomic nervous system, immune system, metabolites, hormones, and neurotransmitters. In addition, the treatments using microbiota that have been tried, to date, are briefly summarized. By understanding the mechanism by which gut-brainmicrobiota regulates blood pressure, the novel targets for hypertension treatment or a new therapeutic approach using the gut-brain-microbiota could be investigated.
Keywords: angiotensin II